Harvard Business Review manager's handbook : the 17 skills leaders need to stand out. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2017)
Whether you are new to being a boss or are simply looking to stand out from the pack, this is the one primer you need to develop your managerial and leadership skills. Packed with step-by-step advice and wisdom from HBR's management archive, the book provides best practices on topics from building credibility and emotional intelligence to hiring and engaging the best employees, as well as understanding key financial statements and the fundamentals of strategy. Keep this comprehensive guide with you as you grow as a leader and you will have a bigger impact in your organization and on your career.--
Part One. Develop a Leader Mindset. 1. The Transition to Leadership. Understanding your role as a manager ; The difference between management and leadership ; Demystifying leadership ; Handling the emotional challenges of the transition -- 2. Building Trust and Credibility. Establishing your character ; Demonstrating your competence ; Cultivating authentic leadership ; Ethics and integrity -- 3. Emotional Intelligence. What is emotional intelligence? ; The power of self-awareness ; Emotional steadiness and self-control ; Managing an employee's emotions ; Building social awareness on your team -- 4. Positioning Uourself for Success. Redefining success ; Understanding your organization's strategy ; Planning for strategic alignment -- Part Two. Managing yourself. 5. Becoming a Person of Influence. Positional versus personal power ; Managing up ; Partnering with your peers ; Silo busting and effectiveness ; Promoting your ideas to others -- 6. Communicating Effectively. Finding your voice as a leader ; Mastering the written word ; Persuasive presentations ; Conducting effective meetings -- 7. Personal productivity. Time management essentials ; Finding focus ; Stress management ; Work-life balance -- 8. Self Development. Career purpose ; Look for opportunities within your organization ; Feedback from your boss and your team -- Part three. Managing Individuals. 9. Delegating with Confidence. Benefits of delegation ; Developing a delegation plan ; Sharing your delegation plan with your employee ; Provide support ; Avoid reverse delegation -- 10. Giving Effective Feedback. Giving feedback in real time ; Giving difficult feedback ; Coaching and developing employees ; Performance reviews -- 11. Developing Talent. Employee development as a priority ; Creating career strategies with your staff ; Developing high-potential talent ; Stretch assignments -- Part Four. Managing Teams. 12. Leading Teams. Team culture and dynamics ; Managing cross-cultural teams ; Managing virtual teams ; Productive conflict resolution -- 13. Fostering Creativity. Plan a creative session ; Tools for generating ideas ; Making sure all perspectives are heard ; Dealing with negativity -- 14. Hiring -- and Keeping -- the Best. Crafting a role ; Recruiting world-class talent ; Retaining employees ; Motivation and engagement -- Part Five. Managing the Business. 15. Strategy : A Primer. Your role in strategy ; What is strategy? ; Developing your strategy ; Leading change and transitions -- 16. Mastering Financial Tools. The basics of financial performance ; Understanding financial statements ; Budgeting -- 17. Developing a Business Case. Stakeholder perspectives ; Clarifying the need and value ; Cost/benefit analysis ; Risk identification and mitigation ; Writing your business case ; Getting buy-in for your plan -- Epilogue.
Includes bibliographical references (pages 315-327) and index.
Keywords: Management -- Handbooks, manuals, etc; BUSINESS & ECONOMICS / Personal Success; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management; Handbooks and manuals; Handbooks and manuals